Single case evaluation of a school-based feeding program for A.Y. 2018-2019 - Fernando, Zyra Mae C. (College of Home Economics, University of the Philippines Diliman, 2021)
High rate of child poverty is a rising concern across the globe particularly in the Philippines. In line with that, School-based Feeding Program (SBFP) is one of the government interventions which aims to solve this problem. SBFP intends to distribute food and ease child hunger to encourage them to attend to school and improve their grades. The purpose of this research is to evaluate the nutritional and educational outcomes of School-based Feeding Program (SBFP) in Burgos Elementary School Unit 1 in terms of the BMI, class attendance and grades of the student-beneficiaries for the SY 2018-2019. This study also attempts to determine the student-beneficiaries’ parents’ perceived effects of the discontinuance of feeding caused by the pandemic. The study used quantitative non-experimental causal comparative research method design. Three t-tests with 0.05 level of significance, were conducted to test the differences in the BMI, class attendance and grades of the student-beneficiaries. It also used a survey to parents of student-beneficiaries, to obtain their perceived effects on the discontinuance of SBFP. The survey questionnaire consisted of a Likert scale focused on the nutritional and educational outcomes of the student-beneficiaries. Based on paired sample t-test analysis at 0.05 level of significance, the study revealed that there was a significant difference between the pre and post BMI measurements of SBFP student-beneficiaries, as regards to their nutritional status. In terms of the educational outcomes, based on the t-tests and Mann-Whitney U test of difference, at 0.05 level of significance, the study showed that there was a significant difference between the grades of student-beneficiaries and non-beneficiaries but no significant difference on the class attendance. These signify that SBFP improved the nutritional status and grades of student-beneficiaries but it has no significant effect on their class attendance. Meanwhile, results from the 4-point Likert scale survey to the parents of the student-beneficiaries showed both agreement and disagreement from the parents that the discontinuance of SBFP has an effect on the nutritional status, class attendance and grades of their child-beneficiaries. Despite of that, parents generally view SBFP as essential and beneficial where they anticipate its continuous implementation. Based on these major findings, this study recommends to expand the SBFP evaluation of nutritional and educational outcomes on a larger scale to validate the results of the study. It also recommends for the Department of Education to develop an evaluation manual that will guide the implementers to a standard monitoring procedures, methods and assessment, and to create actions that will urge the parents of student beneficiaries to have a closer involvement and awareness of the benefits of SBFP to their children.